1998
DOI: 10.1007/978-94-011-5118-4_107
|View full text |Cite
|
Sign up to set email alerts
|

On Geometrical Alignment Properties of Two-Dimensional Forced Turbulence

Abstract: In the present paper we study some geometrical properties of the small scales in 2D numerical turbulence. We analyze the alignment of the vorticity gradient with respect to the eigenvectors of the rate of strain tensor, a phenomenon related to the dynamics of the enstrophy cascade. Numerical simulations with different resolutions and dissipation models are used to show non-trivial dependence of the alignment on both the magnitude of the vorticity gradient and the Reynolds number. These findings are shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The difference between active (vorticity) and passive tracer dynamics has been further investigated by looking at the geometrical alignment of tracer gradients. In two-dimensional turbulence, Protas, Babiano & Kevlahan (1999) numerically confirmed that the production of vorticity gradients by stirring depends on the relative orientation between the gradient itself and the compressional axis of the rate-of-strain tensor (Weiss 1991). Kimura & Herring (2001) studied vortex filament ejection following the gradient enhancement process for vorticity.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The difference between active (vorticity) and passive tracer dynamics has been further investigated by looking at the geometrical alignment of tracer gradients. In two-dimensional turbulence, Protas, Babiano & Kevlahan (1999) numerically confirmed that the production of vorticity gradients by stirring depends on the relative orientation between the gradient itself and the compressional axis of the rate-of-strain tensor (Weiss 1991). Kimura & Herring (2001) studied vortex filament ejection following the gradient enhancement process for vorticity.…”
Section: Introductionmentioning
confidence: 83%
“…In terms of geometrical alignment properties, the above results indicate that in small-scale elliptic patches the two backward cascades should lead to a statistical anticorrelation between ∇ω and the stretching direction due to the larger-scale strain field. Unfortunately, a direct estimate of the alignment properties can be difficult, as the limits of the numerical resolution and the application of low-pass filtering precedures can hamper the detection of alignment properties at the filter scale (Protas et al 1999, see also Dubos & Babiano 2002.…”
Section: Gradient-decreasing Processes and Inverse Energy Transfermentioning
confidence: 99%
“…In rotation-dominated regions (II > 0), P oscillates between positive and negative values. Physically, ∇ω rotates and alternates between amplification and damping, a condition which results in elliptic instability (Protas, Babiano & Kevlahan 1999). We expect the dynamic effect of P on ∇ω to be most significant in strong strain-dominated regions (II < 0), i.e.…”
Section: Vortex Merging: Unstratified Flowmentioning
confidence: 97%
“…It is well known that the two-dimensional dynamics of a passive scalar is generically characterized by geometrical alignments of the scalar gradient with preferred directions prescribed by the flow (Okubo 1970;Weiss 1991;Protas, Babiano & Kevlahan 1999;Lapeyre, Klein & Hua 1999;Klein, Hua & Lapeyre 2000). It is therefore natural to try to distinguish active and passive scalars using their alignment properties in connection with a complex distribution of strain.…”
Section: Introductionmentioning
confidence: 99%